Polymers from Renewable Resources - Siracusa, Valentina; Lotti, Nadia; Soccio, Michelina; Iordanskii, Alexey (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The aim of this reprint is to provide more awareness of the use of bioplastics obtained from renewable resources in numerous aspects of our daily used items. This reprint presents recent progress in the use of innovative feedstock, full characterization of new biomaterials and innovative technologies used to produce innovative sustainable materials.